Intraoperative neurophysiologic monitoring alteration during en bloc laminectomy surgery for thoracic ossification of ligamentum flavum - Feng, Xiaoning; Deng, Li; Feng, Haoyu; Hu, Yong; Tian, Jianghua; Sun, Lin (Frontiers in Surgery, 2022)
Abstract Background: There is real risk during en bloc resection for the treatment of thoracic ossification of ligamentum flavum (TOLF). Intraoperative neurophysiologic monitoring (IONM) has been applied to monitor neurologic functional integration of the spinal cord during surgery. However, the IONM outcome and its relationship with clinical results still needs to be investigated. The purpose of this study is to evaluate the effectiveness and usefulness of IONM in en bloc laminectomy for TOLF. Methods: Data from a total of 68 patients with TOLF who received en bloc resection was collected for this retrospective study. IONM of somatosensory-evoked potentials (SSEPs) and motor-evoked potentials (MEPs) were analyzed in different patterns of signal alerts, i.e. alert in either MEPs or SSEPs, alert in both MEPs and SSEPs, permanent alert, or recovery during surgery. Postoperative motor and sensory neurological function was evaluated in each patient immediately after surgery and at 12-month follow-up after surgery. The relationship of IONM outcomes and postoperative neurologic function were observed. Results: Fifty of 68 patients did not present significant changes over alert criteria of IONM, neither SSEPs nor MEPs. Those 50 patients without IONM alerts did not show post-operative neurologic deterioration. Four patients presented alert of IONM in a single modality, while 2 patients showed only SSEP alert and 2 patients showed only MEP alert. Fourteen patients showed alerts in both SSEP and MEP, while 8 patients showed one or both signals return to normal during surgery and other 6 showed permanent abnormal electrophysiologic signals to the end of surgery. In the follow-up neurologic test, 3 patients presented transient neurologic complications from among 8 patients with both SSEP and MEP alerts and recovery during surgery. Six patients without recovery of IONM showed permanent neurologic complications after surgery. Conclusions: Results of this study prove the effectiveness and usefulness of IONM in in en bloc laminectomy surgery for TOLF. The patterns of IONM changes correlated with postoperative neurologic functions. Special attention must be paid to the rapid loss of IONM without recovery during spinal decompression.